Peter Lombard’s Theology of Marriage: Insights from the Sentences - Jin, Yuan (Asian Horizons, 2024)
This article explores Peter Lombard’s understanding of marriage, examining his theological framework, perspectives on matrimonial consent, and the significance he attributes to this sacred union. Through a comprehensive examination, this article elucidates the complexities and intricacies of Lombard’s thought, delving into the sacramental nature of marriage, marital duties, and the indissolubility of the marital bond. The analysis not only highlights Lombard’s distinctive theological stance but also facilitates a deeper understanding of the historical development of Catholic teachings on marriage. Furthermore, this article explores Lombard’s interaction with societal conventions, legal implications, and the practical application of theological principles in the matrimonial context of his time. By integrating historical theology with the analysis of social and legal dimensions, this study contributes a more nuanced appreciation of the interplay between Church teachings and marital practices in the medieval period.